Implementasi Manajemen Proyek Pada Pengembangan Website Pemetaan Biodiversitas Tanaman Obat Di Kabupaten Kediri - Muhammad Iqbal Khalid; Rina firliana; Sucipto; Anita Sari Wardani; M Najibuloh Muzzaki5; Adhi Wicak Milbar Gamas; Shandy Arshad Busro Cahyono; Heru Stiawan (Bulletin of Information Technology (BIT), 2022)
The creation of a website for mapping medicinal plants and rare plants in Kediri Regency is a collaborative program between the regional Balitbang and Universitas Nusantara PGRI Kediri under the auspices of the Matching Fund. In a software development project that is closely related to SDLC (Stem Development Life Cycle) in its application there are several methodologies including the waterfall which is carried out in stages in a systematic and sequential manner, this is a problem for the use of the waterfall method. Over time, a new methodology called Scrum was discovered which is more flexible or adaptive because it is iterative and incremental. Therefore, the purpose of this study is to test how effective the use of the Scrum methodology is in managing website development projects